2019
DOI: 10.1200/po.19.00123
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Androgen Receptor Copy Number Status at Emergence of Metastatic Castration-Resistant Prostate Cancer: A Pooled Multicohort Analysis

Abstract: PURPOSEIncreases in androgen receptor ( AR) copy number (CN) can be detected in plasma DNA when patients develop metastatic castration-resistant prostate cancer. We aim to evaluate the association between AR CN as a continuous variable and clinical outcome.PATIENTS AND METHODSPCR2023 was an international, multi-institution, open-label, phase II study of abiraterone acetate plus prednisolone (AAP) or abiraterone acetate plus dexamethasone that included plasma AR assessment as a predefined exploratory secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…After normalization to the averaged combined reference control, we observed the median Log2 CN ratio, being 0.52 (range −1.42–6.00) for AR -En, 0.29 (range −1.69–5.45) for AR -E1, 0.36 (range −0.92–5.45) for AR -E8, and 0.14 (range −1.54–5.04) for OPHN1 ( Figure 2 A). We defined the amplification as the normalized CN ratio ≥ 1.92 between the targets and reference loci using a suggested threshold [ 29 ] and our previously reported observations made in an independent mCRPC cohort [ 4 ]. Among the 108 mCRPC patients, 28 (25.9%) had AR enhancer amplification; 24 (22.2%) had AR- E8 amplification; 25 (23.1%) had AR -E1 amplification; and 19 (17.6%) had OPHN1 amplification ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After normalization to the averaged combined reference control, we observed the median Log2 CN ratio, being 0.52 (range −1.42–6.00) for AR -En, 0.29 (range −1.69–5.45) for AR -E1, 0.36 (range −0.92–5.45) for AR -E8, and 0.14 (range −1.54–5.04) for OPHN1 ( Figure 2 A). We defined the amplification as the normalized CN ratio ≥ 1.92 between the targets and reference loci using a suggested threshold [ 29 ] and our previously reported observations made in an independent mCRPC cohort [ 4 ]. Among the 108 mCRPC patients, 28 (25.9%) had AR enhancer amplification; 24 (22.2%) had AR- E8 amplification; 25 (23.1%) had AR -E1 amplification; and 19 (17.6%) had OPHN1 amplification ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the association of AR-E1 with OS was changed to significant from insignificant ( p value from 0.08 was changed to 0.02). However, to stay consistent with the recently published cutoff call rates on amplification status [ 29 ], we selected 1.92 as the cutoff value for amplification calls.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio (HR) for each age bracket was calculated relative to the baseline bracket (15–20 years) using a Cox regression stratified by centre and single age cut-offs corresponding to the highest increase in HR were selected for evaluation, and the proportionality assumption tested using Schoenfeld residuals. Log-likelihood was used as a correlative measure for determining the optimal cutpoint [ 14 ]. Classification and Regression Tree Analysis (CART) was used as an alternative method for automatic identification of optimal cut-offs and the results from both approaches were compared [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it is still controversial whether the level of CN gain has any impact on clinical outcomes. A recent meta-analysis [21] described a nonlinear relationship between plasma AR CN and survival, while Annala et al [22] showed a different response to abiraterone/enzalutamide for patients with high AR gain (>8 copies) compared with low AR gain (two to eight copies), indicating a possible dose-response effect in overcoming inhibition of AR signalling using AR-directed therapies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%